The Local Wisdom of Floating Market Traders in Supporting Honest and Fair Trade - Yuli Apriati; Dasim Budimansyah; Chairil Faif Pasani; Encep Syarief Nurdin (Universitas Pendidikan Ganesha, 2024)
Although in traditional trade practices, unethical practices are increasingly occurring, characterized by a lack of principles of honesty, trustworthiness, and transparency among traders, on the contrary, in traditional river-based trade practices at the Lok Baintan floating market with local wisdom